Penelaahan Alkitab Induktif Sebagai Model Hermeneutik: Studi Kualitatif Metode O.I.A. Dalam Perumpamaan Injil Matius - Hendrik, Hendrik; Waani, Marciano Antaricksawan; Marini, Roberth Ruland (JURNAL KADESI, 2026)
Biblical interpretation constitutes a significant component of Christian theological studies because it is directly related to the effort to understand the Word of God accurately and responsibly. However, the differences in historical, cultural, linguistic, and literary contexts between the world of the Bible and contemporary readers necessitate a hermeneutical method capable of bridging these gaps. This article aims to examine inductive Bible study through the Observation, Interpretation, Application (OIA) method as a hermeneutical model for interpreting the parables in the Gospel of Matthew. This study employs a qualitative–descriptive approach using a literature review method, drawing on various hermeneutical sources, commentaries on the Gospel of Matthew, and relevant works of biblical theology.The findings indicate that the OIA method provides a systematic and practical framework for the interpretive process, beginning with careful textual observation, followed by interpretation based on historical and theological contexts, and culminating in the application of the text’s meaning to contemporary life. In the context of the Matthean parables, this method proves particularly relevant because the symbolic and contextual nature of parables, as well as their focus on the teaching of the Kingdom of God, requires a careful and non-speculative reading. The OIA approach also assists readers in avoiding the tendency toward excessive allegorization and subjective interpretations detached from the original intent of the text. Furthermore, this method demonstrates a balance between academic understanding and spiritual transformation, ensuring that biblical study not only produces knowledge but also encourages spiritual growth and faithful obedience. Nevertheless, this study also emphasizes that the OIA method should be enriched by other hermeneutical approaches in order to produce more comprehensive interpretations. Therefore, inductive Bible study through the OIA method may be regarded as a relevant and applicable hermeneutical model for the church, theological education, and personal Bible reading in the pursuit of understanding and living out the values of the Kingdom of God in a contextual manner.